PENGARUH KUALITAS PRODUK, PERSEPSI HARGA,DAN CITA RASA UNTUK MENINGKATKAN KEPUASAN PELANGGAN CAFE BELI KOPI DI BUBUTAN SURABAYA - Putri Ayu Zakiya; Yuliar Kartika Wijayanti (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to test and analyze the influence of product quality, price perception, and taste to increase customer satisfaction at Cafe Beli Kopi in Bubutan Surabaya. This research method uses a quantitative approach. The population in the study includes Beli Kopi consumers consisting of teenagers, students, and adults in the city of Surabaya. Because the population size cannot be known with certainty, the determination of the number of samples is carried out using the Lemeshow formula (Riyanto Slamet, 2020:13). The sample used in this study was 100 respondents,namely Beli Kopi consumers in the Bubutan area, Surabaya. The analysis techniques used include descriptive analysis, validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing with the help of IBM SPSS Statistics software.